Comparative assessment fire resistance concrete hollow-core slabs using standards of Belarus, Ukraine, the European Union, and computational methods - Golodnov Александр; Kudryashov Вадим; Polevoda Иван; Otrosh Юрий; Tkachuk Игорь; Seminog Николай; Drobysh Антон (Vestnik of the Institute for Command Engineers of the MES of the Republic of Belarus, 2015)
Fire resistance standards for test structures comparison of Ukraine, Belarus and the European Union, as well as multiple fire test data of the most common reinforced concrete hollow-core slabs is analyzed in the article. The fire resistance test results for prestressed concrete hollow core slabs in comparison with fire resistance design methods are presented.